2015
DOI: 10.1515/biolog-2015-0096
|View full text |Cite
|
Sign up to set email alerts
|

Structural and phylogenetic analysis of α-glucosidase protein in insects

Abstract: α-Glucosidases (αglus) (EC 3.2.1.20) have been detected in a wide range of plants, animals and microorganisms and are described by their ability to catalyze the hydrolysis of 1,4-α-glucosidic linkages, releasing α-glucose. In this study, 96 αglu protein sequences from 33 organisms species including different insects species, plants (including thale cress and rice), mammals (including human and mouse) and Mycobacterium tuberculosis as a bacterium were aligned. Sequences were analyzed by computational tools to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 85 publications
(87 reference statements)
2
2
0
Order By: Relevance
“…The α‐helix was found to decrease with the increase in curcumin ratio while the β‐sheet was increased. These results were consistent with the similar reported conclusion suggesting that the inhibitor could change the secondary structure of α‐glucosidases protein (Seddigh & Darabi, 2015).…”
Section: Resultssupporting
confidence: 93%
“…The α‐helix was found to decrease with the increase in curcumin ratio while the β‐sheet was increased. These results were consistent with the similar reported conclusion suggesting that the inhibitor could change the secondary structure of α‐glucosidases protein (Seddigh & Darabi, 2015).…”
Section: Resultssupporting
confidence: 93%
“…In this study, we predicted the tertiary structure and sucrose binding sites of BmSUH using Phyre2 and 3DLigandSite software 29 30 . Our predicted result was concordant with the estimation of Seddigh, who conducted homology modelling of α-glucosidase, such as Dm-NP610382 ( D. melanogaster ), Am-XP006560868 ( A. mellifera ), At-NP196733 ( A. thaliana ), Hs-NP937784 ( H. sapiens ) and Mt-YP007966392 ( M. tuberculosis ) 41 . This similarity of tertiary structure prediction analysis indicated that the 3D structures of α-glucosidase are conserved during evolution.…”
Section: Discussionsupporting
confidence: 89%
“…A disulfide bond connects the A domain to the C domain, the function of which remains unknown. 6 Glycoside hydrolases are important enzymes that can increase the hydrolysis rate of polysaccharides to 10 17 times and provide nutrition and development for organisms. 7 The αamylases belonging to the family GH 13 are famous, for having excellent substrate specificity and efficient catalytic ability, which can effectively improve the utilization rate and production efficiency of starch raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…B is the second large domain located between C and A. A disulfide bond connects the A domain to the C domain, the function of which remains unknown …”
Section: Introductionmentioning
confidence: 99%